ANALISIS KESESUAIAN LAHAN KABUPATEN PEKALONGAN BERDASARKAN SISTEM INFORMASI GEOGRAFIS - Agus Sarwo Edy Sudrajat (Indonesian Journal of Spatial Planning, 2020)
As time goes by, a city or region will change its physical appearance. Visually, the physical appearance of the city can be seen from the growth of the center of activity and population activities that occupy a land space both vertical and horizontal developments. The realization of this is the impact of increasing population and growing population activities. Society or population as perpetrators as well as objects of development is one of the main actors influencing changes in a city or region. Of course this will have implications for the needs of land as a space for socio-economic and ecological activities.From the description above, it can be explained further, that the needs of this land if it is not considered in a balanced manner between demand and supply will have a negative impact on the land itself, including for human beings. Land needs are increasing while the amount of land is limited, so there is often a change in land use that is not in accordance with its designation.Therefore, in each land change, an analysis of the land is needed to determine the function (suitability) and character (capability) of the land so that any changes in land use can be known to be feasible and then the appropriate land use direction can be known. The method used is the spatial method using the map overlay technique with geographic information system software. With this method, it is expected to provide a detailed and precise description of the function and character of the land so that the direction of the development of a city or region can be determined optimally effectively and efficiently while anticipating the emergence of land change conflicts.